Barriers to Optimal Acute Management of Stroke: Perspective of a Stroke Center in Mexico City - Cano-Nigenda, Vanessa; Castellanos-Pedroza, Enrique; Manrique-Otero, Diana; Méndez, Beatriz; Menéndez-Manjarrez, María Fernanda; Toledo-Treviño, Roberto; Calderón, Miguel; Arauz, Antonio (Frontiers in Neurology, 2021)
Background: Stroke is a leading cause of death and disability worldwide, particularly in low- and middle-income countries. We aimed to identify the main barriers to optimal acute management of stroke in a referral center. Methods: Demographic data was collected from patients assessed with acute stroke in the emergency department of the Instituto Nacional de Neurología y Neurocirugía(INNN) from January to June 2019. Additionally, a telephone interview was conducted with patients/primary caregiver to know which they considered the main reason for the delay in arrival at INNN since the onset of stroke. Results: 116 patients were assessed [age 65±15 years, 67 (57.8%) men]. Patients consulted other facilities prior to arrival at INNN in 59 (50.9%) cases (range of hospitals visited 1–4), 83 (71.6%) arrived in a private car, with prenotification in only 4 (3.4%) of the total sample. The mean onset-to-door time was 17h (45 min–10 days). Telephone interviews were done in 61 patients/primary caregivers, stating that they consider the multiple evaluations in other facilities [n=26/61, (42.6%)] as the main reason for delay in arrival at the ED, followed by ignorance of stroke symptoms and treatment urgency [n=21/61 (34.4%)]. Conclusion: In this small, retrospective, single center study, the main prehospital barrier to optimal acute management of stroke in a developing country is multiple medical evaluations prior to the patient’s transport to a specialized stroke hospital, who mostly arrived in a private car and without prenotification. These barriers can be overcome by strengthening public education and improving patient transfer networks and telemedicine.